Role of Microfinance in Socio-Economic Development in Nepal (TUTA Journal, 2024)
No systematic effort to map the distribution of microfinance has yet been undertaken. A benchmark was established by an analysis of 'alternative financial institutions' in the developing world in 2004. The authors counted approximately 665 million client accounts at over 3,000 institutions that are serving people who are poorer than those served by the commercial banks. Of these accounts, 120 million were with institutions normally understood to practice microfinance. Reflecting the diverse historical roots of the movement, however, they also included postal savings banks (318 million accounts), state agricultural and development banks (172 million accounts), financial cooperatives and credit unions (35 million accounts) and specialized rural banks (19 million accounts). Regionally, the highest concentration of these accounts was in India (188 million accounts representing 18% of the total national population). The lowest concentrations were in Latin America and the Caribbean (14 million accounts representing 3% of the total population) and Africa (27 million accounts representing 4% of the total population, with the highest rate of penetration in West Africa, and the highest growth rate in Eastern and Southern Africa Considering that most bank clients in the developed world need several active accounts to keep their affairs in order, these figures indicate that the task the microfinance movement has set for itself is still very far from finished. This paper attempts to study the role of Micro-Finance in socio- economic empowerment.